Landscape Connectivity Modeling for Conservation Planning (International Journal of Animal Biodiversity, Conservation and Systematics ( IJABC), 2023)
Landscape connectivity modelling -- the quantitative assessment of the degree to which landscape structure facilitates orimpedes animal movement between habitat patches -- is an essential tool in conservation planning. This studybenchmarked six connectivity models -- least-cost path (LCP), Circuitscape (CS), UNICOR, Linkage Mapper,Omniscape, and graph-theoretic betweenness centrality (GBC) -- against empirical GPS telemetry movement data andpopulation genetic FST from 12 species across Iberian Peninsula landscapes (284 GPS-tracked individuals; 48population pairs; 28,484 SNPs per species). Circuitscape with empirically calibrated resistance surfaces achieved thehighest corridor prediction overlap (CPO = 0.74 +- 0.08) and IBR correlation (r(S) = +0.84 +- 0.06). Omniscapeperformed comparably (CPO = 0.72; r(S) = +0.82) while producing spatially continuous maps better suited to land-useplanning. LCP performed lowest (CPO = 0.48; r(S) = +0.54). Step selection function (SSF) resistance surface calibrationimproved all model performance by 18.4-24.4% over expert-estimated generic surfaces. These results confirmCircuitscape as the optimal tool for corridor identification, Omniscape for planning without patch data, and demonstratethat empirical resistance calibration is the highest-return investment for connectivity model improvement.